Can a rescuer or simulated patient accurately assess motion during cervical spine stabilisation practice sessions?. Issue 4 (27th March 2011) - Shrier, I; Boissy, P; Fecteau, L; Mellete, J; Steele, R; Matheson, G O; Garza, D; Meeuwisse, W H; Segal, E; Boulay, J
Abstract : Background: Proper stabilisation of suspected unstable spine injuries is necessary to prevent (worsen) spinal cord damage. Almost all training relies on subjective reports from the simulated patient or observations from an independent person. The reliability and validity of these measures remains unknown. Objective: To determine 1) how accurately rescuers and simulated patients assess motion during cervical spine (c-spine) stabilisation practice, and 2) if providing feedback on performance influences behaviour preferences. Design: Cross-over design. Setting and Participants: 12 experienced therapists. Assessment: Head Squeeze and Trap Squeeze (random order) c-spine stabilisation during four test scenarios: lift-and-slide (L&S) and log-roll (LR) placement on spinal board, and agitated patient trying to sit up (AGIT-SIT) or rotate head (AGIT-ROT). Main outcome measurements: Inter-rater reliability between rescuer and simulated patient quality scores for subjective evaluation of c-spine stabilisation during trials (0=best, 10=worst), correlation between rescuers' quality score and objective measure of motion with inertial measurement units (IMU), and frequency of change in preference for Head Squeeze vs Trap Squeeze. Results: Although the weighted-kappa for inter-rater reliability was acceptable (0.71–0.74), scores varied by more than one points between rescuers/simulated patients for ∼10–15% of trials. Rescuers' scores correlated with objective measures but with large variability. For example, 38% of trials scored as almost perfect (0–1) by the rescuer actually had >10° of motion in at least one direction. In general, feedback did not affect preference for L&S. For the LR, 6/8 subjects preferring Head Squeeze at baseline preferred Trap Squeeze after feedback. For the confused patient, 5/5 subjects preferring Head Squeeze at baseline preferred Trap Squeeze after feedback. Conclusion: Rescuers and simulated patients could not adequately assess performance during c-spine stabilisation without objective measures. Providing immediate feedback is a promising tool for teaching proper technique and for changing preferences of behaviour in this context.